2015
DOI: 10.4236/nr.2015.64020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Effects of Nitrogen and Sulphur Starvation in <i>Chlorella sorokiniana</i> 211/8K

Abstract: Nitrogen (N) and sulphur (S), being essential macronutrients, have important roles in microalgae metabolism. Effects of N-or S-shortage were investigated in the green microalgae Chlorella sorokiniana subjected to 24 h of starvation, by measuring the glutamine synthetase (GS) and O-acetylserine(thiol)lyase (OASTL) activities, proteins and amino acids levels. To test possible metabolic impact related to carbon (C) metabolism in response to N-or S-deprivation, starch and total C, N and S contents were also determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The lower number of filaments, biomass, cell productivity and maximum specific growth rate at lower concentration of K 2 SO 4 (0.16 g/L) are in agreement with those reported by Wagih El-Shouny et al (2015) which showed that the reduction of sulphur in the culture medium involved non significant reduction in the growth of the biomass and productivity of S. platensis. Moreover low yield of growth recorded in media in with low potassium sulphate concentrations could be because sulphur deficiency could cause a reduction in the cell multiplication while influencing on metabolism of carbon in photosynthetic activity as reported by Carfagna et al (2015) to Chlorella sorokiniana. Therefore, in media supplemented with different concentrations of sulphate salts, the best number of filaments, biomass, cell productivity and maximum specific growth rate were recorded on medium supplemented with MgSO 4 /K 2 SO 4 (0.02/0.14 g/L).…”
Section: Discussionmentioning
confidence: 95%
“…The lower number of filaments, biomass, cell productivity and maximum specific growth rate at lower concentration of K 2 SO 4 (0.16 g/L) are in agreement with those reported by Wagih El-Shouny et al (2015) which showed that the reduction of sulphur in the culture medium involved non significant reduction in the growth of the biomass and productivity of S. platensis. Moreover low yield of growth recorded in media in with low potassium sulphate concentrations could be because sulphur deficiency could cause a reduction in the cell multiplication while influencing on metabolism of carbon in photosynthetic activity as reported by Carfagna et al (2015) to Chlorella sorokiniana. Therefore, in media supplemented with different concentrations of sulphate salts, the best number of filaments, biomass, cell productivity and maximum specific growth rate were recorded on medium supplemented with MgSO 4 /K 2 SO 4 (0.02/0.14 g/L).…”
Section: Discussionmentioning
confidence: 95%
“…The obtained results coincided with the results reported by Zalutskaya et al [ 48 ] on Chlamydomonas reinhardtii , where any stimulus (as sulfur starvation) causes the cytochrome-pathway complex dysfunction in mitochondrial electron transport chains, which led to the induction and expression of alternative oxidase 1 and 2 genes. Moreover, under sulfur starvation condition, photosynthetic activity and metabolism are affected [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Copyright © 2017 The Authors; exclusive licensee Bio-protocol LLC. 6 3. OASTL activity was expressed in units that correspond to the formation of 1 µmol of cysteine min -1 .…”
Section: Discussionmentioning
confidence: 99%